The Impact of Corporate Governance and Ownership Structure on Bank Performance - Tayar , Hussain; Kardan , Behzad; Salehi , Mahdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study investigates the impact of corporate governance and ownership structure on the performance of banks listed on the Tehran Stock Exchange during the period from 2012 to 2021.Methodology: The research method is of a survey type and utilizes financial information and annual reports of the banks. Data extraction and necessary statistical tests were conducted. In this study, three performance indicators were used: Return on Assets (ROA), Return on Equity (ROE), and Tobin's Q. The research method is descriptive-causal, and the design is experimental using a post-event approach. For data analysis, statistical and econometric methods, particularly multiple regression, were employed.Findings: The results indicate that among the corporate governance criteria, board independence, board size, and audit firm size have the most significant impact on bank performance and play a crucial role in improving performance. In contrast, CEO duality and the relationship and holding management have less impact. Additionally, a positive and significant relationship was observed between board independence and audit firm size with bank performance. In the context of ownership structure, top shareholders and ownership concentration were identified as the most influential criteria.Conclusion: These criteria play an important role in the ownership structure of banks. Conversely, domestic private ownership, foreign ownership, and managerial ownership have less impact compared to other criteria. Furthermore, a negative and significant relationship was observed between ownership concentration and bank performance, indicating that high ownership concentration may lead to a decrease in bank performance. This study highlights the importance of specific corporate governance and ownership structure